2016
DOI: 10.11648/j.ajns.20160503.16
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Physical Stretching Exercise on Feto-Maternal Outcomes Among Mild Preeclamptic Pregnant Women in Egypt

Abstract: Preeclampsia is a disorder of widespread vascular endothelial malfunction and vasospasm that occurs after 20weeks' gestation. It accounts for 22% of maternal deaths, 18% of all pre-mature births worldwide. Recently, recommendations about exercise in pregnant women with hypertension or at risk of pre-eclampsia (PE) development have been studied with the objective of trying to reduce the deleterious effects of hypertensive disorders in pregnancy, including the reduction of the incidence of PE. This study aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
0
1
Order By: Relevance
“…These authors also reported 9.4% of fetal deaths associated with severe complications, which is similar to our findings; we noted that 11.1% of neonatal deaths were due to respiratory tract syndrome, low birth weight, and other related complications [17]. In a study conducted at the El-Shatby Maternity University Hospital in Alexandria, it was concluded that 4.4% of the babies had low birth weights, and this aligns with the findings of the present study in which 4.45% of the babies had low birth weights [18].…”
Section: Table 12: a Comparison Of Sociodemographic Characteristics O...supporting
confidence: 92%
See 1 more Smart Citation
“…These authors also reported 9.4% of fetal deaths associated with severe complications, which is similar to our findings; we noted that 11.1% of neonatal deaths were due to respiratory tract syndrome, low birth weight, and other related complications [17]. In a study conducted at the El-Shatby Maternity University Hospital in Alexandria, it was concluded that 4.4% of the babies had low birth weights, and this aligns with the findings of the present study in which 4.45% of the babies had low birth weights [18].…”
Section: Table 12: a Comparison Of Sociodemographic Characteristics O...supporting
confidence: 92%
“…A study held at the Gandhi Memorial Hospital in Ethiopia concluded that preeclampsia was associated with sociodemographic characteristics such as gestational weeks, age, and economic status [14]. In the present study, 52.3% of patients were housewives by occupation, and this was lower (%) than the finding in the study at the El-Shatby Maternity University Hospital in Alexandria where 57.8% of women were housewives [18]. A much higher figure was observed by Mou et al in 2021 [10].…”
Section: Table 12: a Comparison Of Sociodemographic Characteristics O...contrasting
confidence: 81%